Practical deep learning : a Python-based introduction - Kneusel, Ronald T. (No Starch Press, 2021)
"An introduction to machine learning and deep learning for beginners. Covers fundamental concepts before presenting classic machine learning models, neural networks, and modern convolutional neural networks. Includes hands-on Python experiments for each model"--